ANALYSIS EFFICIENCY MARKETING SYSTEM OF FRESH LAYANG FISH (Decapterus russeli) ON PELABUHAN FISH AUCTION PLACE IN TEGAL CITY - Gofar Ismail; Suprapti Supardi; Sri Wahyuningsih (Universitas Wahid Hasyim, 2008)
Marketing is an important aspect in running fishing business because it is an economic activity that influences the fluctuation of fishermen’s income. The production can be useless if the price is low, thus, marketing has to be good and efficient. This research is about the efficiency of the marketing system of fresh fish layang (Decapterus russeli) in the fish auction place. Specifically, this research is to know : 1) the marketing system of fresh fish layang in Tegal City. 2) the marketing margin of fresh fish layang in Tegal City. 3) the distribution flow of fresh fish layang in Tegal City. 4) the reason fishermen sell their products in the Fish Auction Place. The method use in this research is descriptive analysis method, The registration data and literature study. Based on the analysis, it is known that the marketing system of fresh in the Fish Auction Place, seen from the marketing cost calculation, purchasing price, selling price and profit is < 1, which means efficient. And if seen from the marketing margin, the most efficient flow is channel 4 (the 4th channel). Meanwhile, the reason why fishermen sell their Fish Auction Place is because of the guarantee that their product will be sold. Fish is a product that is easily broken and rotten. Therefore, the guarantee that the product will be sold, can minimize loss risk for fisherman. Key word : Marketing Efficiency, Fresh Layang Fish, Fish Auction Place.